Air fryer ownership, household food-related task sharing, cooking skills, and mediterranean diet adherence among cohabiting adults in Türkiye: A cross-sectional study - Zeynep Begüm Kalyoncu Atasoy; Eylem Coşkun; Sinem Çekirdekoğlu; Saimenur Durmaz; Halit Tanju Besler (PLoS ONE, 2026)
Air fryers are increasingly used in home kitchens, yet their relationships with domestic culinary labour and diet quality remain unclear. This cross-sectional study included cohabiting adults in Istanbul, Türkiye, with one respondent recruited per household (N = 384; 50% women); 192 participants (50%) reported owning an air fryer. Cooking and food preparation skills were assessed using a validated 33-item scale (14-item cooking skills and 19-item food skills subscales), and Mediterranean diet adherence was assessed using MEDAS. Group comparisons and robust regression models were performed. Compared with non-owners, owners had longer education duration (median 14 vs 12 years) and lower BMI (median 25.7 vs 27.4 kg/m²) (both p < 0.001). Women scored higher than men on cooking skills, food skills, and MEDAS within both ownership strata (all p < 0.01). In robust regression models, air fryer ownership was positively associated with cooking skills (β = 4.253, p = 0.028) and food skills (β = 6.589, p = 0.004). Higher MEDAS scores were associated with older age (β = 0.049 per year, p < 0.001) and regular exercise (β = 1.873, p < 0.001), whereas male sex (β=−1.311, p < 0.001), lower perceived income, and regular smoking were associated with lower MEDAS scores (p < 0.05). Air fryer owners also more frequently reported equal sharing with a spouse for selected routine kitchen tasks, particularly table setting, meal preparation, and dishwashing. Air fryer ownership was associated with higher cooking- and food-skill scores and with more equal sharing of some kitchen tasks, but not with Mediterranean diet adherence.